METHODOLOGY FOR DEVELOPING TECHNICAL MOVEMENTS OF YOUNG FOOTBALL PLAYERS BASED ON KINEMATIC INDICATORS - Mambetiyarov Nauriz Saparbaevich (Proximus Journal Publishing, 2025)
The methodology for the development of technical actions of young players on the basis of kinematic indicators consists of complex processes that require comprehensive thinking and regular work. In order to succeed in the game of football, it is necessary not only to have physical strength and endurance, but also to perform actions in an optimal way, that is, technical skill is also at the highest level. From this point of view, kinematics – an approach based on the science of studying the character, methods and parameters of actions-makes it possible to further study and analyze the technical actions of players. This methodology provides the basis for the effective execution of actions in young players, helps to identify and eliminate their individual mistakes, and serves to develop training aimed at improving technical performance
Keywords: players; technique; kinematic analysis; methods